Some aspects regarding the concept "Research for Business" - Dan Sæavescu (Journal of Industrial Engineering and Management (JIEM), 2010)
Paper presents some aspects regarding the scientific research in universities or research institutes oriented to fundamental or practical aspects. It is known that a researcher must publish his work, but the problems are: publish as single or multiauthors, in ISI or domestic journals, in international proceedings conference having ISBN, to protect the new information as IP national or international organization. The permanent process of research for business, its compulsory steps, the role of innovation and business incubators, are as supporting elements for SME's growth. Beside the facilities offered to SMEs, other benefits come from creating a business incubator, such as: developing innovative products, product design, prototyping, technological transfer and nevertheless, registration and exploitation of intellectual property rights, coming from the obtained products of research. In order to be even more practical, we chose an example of a functional business incubator, ITA Pro-Energ, and showed the facilities that it offers to its incubated SMEs, as well as their improvement on market position.
Keywords: 650; scientific research; incubator; technological transfer; business; sustainable energy